Waist circumference and waist circumference to height ratios of Kaingáng indigenous adolescents from the State of Rio Grande do Sul, Brazil Circunferência da cintura e circunferência da cintura/estatura entre adolescentes indígenas Kaingáng do Rio Grande do Sul, Brasil - Teresa Gontijo de Castro; Laura A. Barufaldi; Michael Maia Schlüssel; Wolney Lisboa Conde; Maurício Soares Leite; Ilaine Schuch (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The aim of this study was to describe the distribution of waist circumference (WC) and WC to height (WCTH) values among Kaingáng indigenous adolescents in order to estimate the prevalence of high WCTH values and evaluate the correlation between WC and WCTH and body mass index (BMI)-for-age. A total of 1,803 indigenous adolescents were evaluated using a school-based cross-sectional study. WCTH values > 0.5 were considered high. Higher mean WC and WCTH values were observed for girls in all age categories. WCTH values > 0.5 were observed in 25.68% of the overall sample of adolescents. Mean WC and WCTH values were significantly higher for adolescents with BMI/age z-scores > 2 than for those with normal z-scores. The correlation coefficients of WC and WCTH for BMI/age were r = 0.68 and 0.76, respectively, for boys, and r = 0.79 and 0.80, respectively, for girls. This study highlights elevated mean WC and WCTH values and high prevalence of abdominal obesity among Kaingáng indigenous adolescents. Os objetivos do estudo foram descrever a distribuição das medidas de circunferência de cintura (CC) e CC/estatura (CC/E) para adolescentes indígenas Kaingáng; estimar a prevalência de valores elevados para CC/E; e avaliar a correlação entre CC e CC/E com o IMC/idade. Um total de 1.803 adolescentes indígenas foi avaliado no estudo seccional de base escolar. Foram considerados elevados valores de CC/E superiores a 0,5. Observaram-se maiores valores médios de CC e CC/E para meninas, em todas as faixas etárias. Valores de CC/E > 0,5 foram encontrados em 25,6% dos adolescentes. Valores médios de CC e CC/E foram significativamente maiores para os adolescentes com IMC/idade > 2 z-scores, em comparação aos eutróficos. Os coeficientes de correlações entre CC e CC/E com o IMC/idade foram: meninos: r = 0,68 e 0,76, respectivamente, e meninas: r = 0,79 e 0,80, respectivamente. Destaca-se proeminência de valores médios elevados de CC e CC/E e prevalências expressivas de obesidade abdominal.